THE CONTROL OF INFORMATION SUPPORT OF THE PROCESSES OF INFLUENCE ON THE OPPONENT - Kubiavka, N.B. (Збірник наукових праць Військового інституту Київського національного університету імені Тараса Шевченка, 2017)
In this research, the classification features of the information impact on interaction contractors knowledge with their individual feature of perception and defines the classes of information representations with a given exposure and counterparty interaction. Base of theory of the non-force interaction gives you opportunity to ground and formally represent scientific and methodological tools of management on impact, which should provide improvement of ways for preparing and conducting operations on the information impact on the enemy, the implementation of countermeasures, that will be most informative and clear, simple, efficient and minimally costly. Also issues of information management are examined not from the position of maximum informing of influenced contractors, but from the position of the necessary information influence on them. Using the proposed classification allows you more accurately and efficiently plan special military operations in the field of information impact on the enemy. This is the main purpose of this study.